(untitled) (Élisée - Revista de Geografia da UEG, 2023)
This research aimed to assess the dynamics of the coastal front occupation in the city of Aracaju/SE, Brazil, based on the delimitation of the occupation phases, associated with the perception of the different settlement patterns. After analyzing nautical charts and mapping the occupation progress, the results showed that from 1970 to 1980, the population flow was redirected towards the coastal front. The first districts to be effectively occupied were Atalaia and Coroa do Meio, the first and second phases of occupation, respectively, followed by the Expansion Zone, which represented the third phase. The fourth phase consisted in verticalizing Atalaia, an unusual pattern for the coastal front until the end of the 2000s, but which has become predominant in the landscape. Regarding settlement patterns, the verticalization process occurred and a concentrated and partially horizontal pattern was identified in Coroa do Meio and Atalaia, as well as dispersed and/or organized occupation in subdivisions in the Expansion Zone. The analysis showed that although the occupation process occurred differently, the logic of occupation in Aracaju’s coastal space was and still is highlighted by the absence of a planning that is consistent with the high fragility of the natural units, which has caused major impacts.